Whatsapp Reminder And Educational Video To Improve Pulmonary Tuberculosis Patient Control Compliance During The Pandemic - Noviyana Pujihastuti; Priyo Priyo; Sigit Priyanto (Media Keperawatan Indonesia, 2022)
Efforts to control tuberculosis in Indonesia have encountered many challenges, including the emergence of the COVID-19 pandemic so the focus of health programs was shifted to dealing with the pandemic. Many tuberculosis patients drop out of control because they are afraid of contracting COVID-19 if they come to the hospital that patient feels worried and decides to postpone the treatment so that it is not controlled according to the schedule given by the nurse/doctor. The purpose of this study was to determine the effect of WhatsApp reminders and educational videos on control compliance of pulmonary tuberculosis patients in the pandemic era at the DOTS Poly Hospital Tidar Magelang City. This study uses a quasi-experimental design with a pre-test and post-test design with a control group design. The sample used was 48 respondents with a random sampling technique. WhatsApp reminder interventions and educational videos were given 4 times in 1 month. The statistical test used was the Shapiro Wilk, Mac Nemar, and Chi-Square tests with significant values (p <0.05). The results showed that there was a significant difference in control compliance before and after being given a WhatsApp reminder and educational video with a p-value: of 0.008 and there was a significant difference in the intervention group and the control group, p-value: 0.016. The conclusion of the study was that there was an effect of WhatsApp reminders and educational videos on the compliance of control of pulmonary tuberculosis patients in the pandemic era at the DOTS Poli, Tidar Hospital, Magelang City.